2017
DOI: 10.1111/phn.12318
|View full text |Cite
|
Sign up to set email alerts
|

Using Twitter to Understand Public Perceptions Regarding the #HPV Vaccine: Opportunities for Public Health Nurses to Engage in Social Marketing

Abstract: Using Twitter to understand public sentiment offers a novel perspective to explore the context of health communication surrounding certain controversial issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 16 publications
0
60
0
Order By: Relevance
“…Time and time again, the safety and effectiveness of HPV vaccination has been confirmed through well-conducted research. However, the spread of misinformation through social media channels [154][155][156][157][158] can overwhelm efforts by public health and medical practitioners to address those misperceptions. With recommendations existing to develop better communications tools, social engagement, and mass media utilization to address vaccine hesitance, 159 we have sought to distill the large amount of HPV-related information available into usable speaking prompts, with supporting references to provide additional information and context.…”
Section: Discussionmentioning
confidence: 99%
“…Time and time again, the safety and effectiveness of HPV vaccination has been confirmed through well-conducted research. However, the spread of misinformation through social media channels [154][155][156][157][158] can overwhelm efforts by public health and medical practitioners to address those misperceptions. With recommendations existing to develop better communications tools, social engagement, and mass media utilization to address vaccine hesitance, 159 we have sought to distill the large amount of HPV-related information available into usable speaking prompts, with supporting references to provide additional information and context.…”
Section: Discussionmentioning
confidence: 99%
“…Over a two-week period in June 2015, 74.2% of the 1,794 tweets about HPV and HPV vaccine analyzed were written by a "lay consumer," and they were almost equally likely to be positive (44.7%) and negative (49.3%). 41 The majority of the content produced by the news media (77.0%), however, were positive. Out of a total of 146 YouTube videos about HPV vaccination analyzed as of February 2008, 70.6% were created by individual YouTube members and 33.9% were from local or national television news coverage.…”
Section: Content Creators and Influencersmentioning
confidence: 97%
“…37 Over a two-week period in June 2015, another study found that the 1,794 tweets analyzed about HPV and HPV vaccine were polarizing, with 50.8% positive, 43.5% negative, and 5.8% neutral. 41 A study of MySpace posts about HPV vaccination between November 2005 and May 2008 found that 52% (n = 157) were classified as positive, 43% (n = 129) as negative, and 6% (n = 17) as ambivalent. 46 In an analysis of the comment sections of news articles about HPV or the HPV vaccine on Canadian news websites in 2012, 630 (52.6%) individuals expressed positive responses about HPV vaccination, while 404 (33.7%) were negative, 34 (2.8%) were mixed, and 130 (10.8%) were neutral.…”
Section: Content Valencementioning
confidence: 99%
See 1 more Smart Citation
“…8 In contrast, Briones et al (2012) found that 33% of videos were provaccine, potentially indicating the increase in anti-vaccine content on YouTube. 6 Similarly, Keim-Malpass et al (2017) found that on Twitter, 51% of the tweets were classified as "positive" and 44% of the Tweets were considered "negative" 14 Similarly, on Pinterest, vaccine side-effects and safety were primary concerns of users. An overwhelming majority of "pinned" images were anti-vaccine (74%) compared to provaccine content (18%).…”
Section: Introductionmentioning
confidence: 99%